Penerapan Sistem Pendukung Keputusan Berbasis Metode SAW Untuk Pemilihan Ketua Himpunan Mahasiswa Fakultas Teknik dan Informatika - Vanya Intan Amabel Adelia; Injil Karmelia Nandey; Dewi Zazinah; Ana Wahyuni (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
An organization's direction and success are greatly influenced by the process of choosing its leaders. However, due to the subjective nature of evaluations, this process often struggles to identify the best candidate. This study aims to elect the Head of the Student Association at the Faculty of Engineering and Informatics using the Simple Additive Weighting (SAW) method as a decision support tool. The SAW method was chosen for its ability to evaluate and rank candidates based on several predetermined criteria. Utilizing a case study and a quantitative approach, data was collected through surveys, interviews, and direct observations. The criteria considered include semester, GPA, organizational experience, recommendations, and previous roles, with each criterion assigned a preference weight. The data was then processed through normalization and weighted summation, revealing that candidate number one achieved the highest score of 0.9895. The study concludes that the SAW method is an effective tool for facilitating objective and data-driven decision-making in the selection of organizational leaders. Keywords: Leadership Selection, Decision Support System, Simple Additive Weighting (SAW)